Strengthening small and medium enterprises (SMES) in tempe production by using entrepreneurial managerial skills - Zuliawati Zed, Etty; Komarudin, Pepen; Irawan, Fajrul; Fadli, M. Nur; Rohana, Siti; Afrah, Mita Fiha; Nusa.T, Ilham (ProBisnis : Jurnal Manajemen, 2024)
The aim of this service is to increase the knowledge and skills of Tempe small and medium enterprises (SMEs) so that they can manage their businesses more efficiently and maintain their competitiveness. Workshops, motivational training, and group mentoring are the ways this service activity is carried out. UKM Tempe, located at Kp.Serang Kota, Rt.11/Rw.06, Suka Dami Village, Cikarang Selatan District, Bekasi, is a community partner in this project. The results of this service show that Tempe SME entrepreneurs have gained better knowledge and skills after receiving training and mentoring. They succeeded in improving their company operations, getting more customers through digital marketing, and forming a Tempe SME group or association to share knowledge and support each other to solve business problems. By strengthening the sector, this initiative increases prosperity and local economic growth.